POLYFACTORIAL CORRUPTION INDEX IN THE RUSSIAN REGIONS: METHODOLOGY OF ESTIMATION - E. L. Sidorenko (Russian Journal of Economics and Law)
Objective: to summarize criminological, social and economic indicators of development of the Russian Federation subjects; to identify and assess the hidden system dependencies between social indicators and levels of corruption; to define the links between individual indicators and to develop the methodology of anti-corruption ranking of the regions.Methods: comparison, analysis, synthesis, mathematical modeling, correlation comparisons and extrapolation.Results: in the work the author describes the methodology of the complex analysis of corruption in the Russian Federation subjects and elaboratesforecasts for its development short term and medium term.Scientific novelty: for the first time in domestic criminology, the algorithm is proposed of studying and forecasting regional corruption on the basis of polyfactorial analysis of criminological, social and political indicators. For profound and comprehensive study of the regional aspects of corruption, a model was developed to monitor and forecast on the basis of measuring the polyfactorial corruption index (PCI). PCI consists of two groups of parameters: corruption potential of the region of the country (CPR) and corruption risk in the region (CRR).Practical significance: the research results can be used in the process of developing regional strategies of corruption counteraction, as well as in adjustment of the existing methods of corruption prevention.